2014
DOI: 10.4161/cbt.29112
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin and 5-fluorouracil induced accumulation and transcriptional activity of p53 are independent of the phosphorylation at serine 15 in MCF-7 breast cancer cells

Abstract: The chemotherapeutic agents doxorubicin (dox) or 5-fluorouracil (5FU) are used to treat cancer cells as they cause irreparable DNA damage, inducing these aberrant cells to undergo cell death. The mediator of this process is presumed to be in part the tumor suppressor p53 which regulates genes involved in DNA repair and cell death. When MCF-7 breast cancer cells are treated with these drugs, we observed that the level of p53 and the p53 negative regulator, Mdm2, increased, as seen by others. But contrary to som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…With elevated concentrations of DOX, p53 and caspase-3 activation was markedly increased to induce apoptosis (Figure 1a). 30, 31, 32 Interestingly, IGF-IIR expression was strongly upregulated, implying that the IGF-IIR signaling pathway may be involved in DOX-induced cardiomyocyte death.…”
Section: Resultsmentioning
confidence: 99%
“…With elevated concentrations of DOX, p53 and caspase-3 activation was markedly increased to induce apoptosis (Figure 1a). 30, 31, 32 Interestingly, IGF-IIR expression was strongly upregulated, implying that the IGF-IIR signaling pathway may be involved in DOX-induced cardiomyocyte death.…”
Section: Resultsmentioning
confidence: 99%
“…AA regulates various signaling pathways for its activities; association with p53 in breast and prostate cancer [ 20 , 24 ], inhibition of Src/FAK/Rho GTPase to block angiogenesis in prostate cancer [ 24 ], and correlation with ATM in squamous cell carcinoma cells of lung [ 25 ]. As for chemotherapeutics, 5-FU was shown to activate p53 [ 26 ] and ATM in colorectal cancer [ 27 ], and GEM to activate p53 in breast cancer [ 20 ]. In addition, we have shown that Chmp1A activates ATM and p53 in pancreatic cancer cells [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Under homeostatic conditions, cellular p53 protein levels are low due to its short half-life and continual degradation by the HDM2 ubiquitin ligase [ 160 , 161 ]. Due to the large proportion of breast carcinomas retaining wt-p53, radiotherapy and chemotherapy agents such as doxorubicin are successful in reactivating p53 via the DNA damage pathway, inducing cell cycle arrest and cell death [ 25 , 26 , 27 ]. In line with its classical role as a tumor suppressor, novel anti-HDM2 (human double minute 2) agents target HDM2, stabilize p53, and reactivate the p53 signaling pathway to kill cancer cells [ 27 , 162 , 163 , 164 ].…”
Section: P53 and Breast Cancer Metabolismmentioning
confidence: 99%
“…Common treatment regimes for breast cancer include surgical ablation, adjuvant or neoadjuvant chemotherapy, radiotherapy, and endocrine therapy, with the therapeutic strategy dependent on the stage and type of cancer [ 24 ]. Radiotherapy and chemotherapy induce DNA damage, inducing cell cycle arrest and apoptosis [ 25 , 26 , 27 , 28 ]. Endocrine therapy, including Tamoxifen and Fulvestrant, blocks the ERα receptor, which in turn represses aberrant estrogen signaling [ 21 ].…”
Section: Introductionmentioning
confidence: 99%